WESTERN BALKANS THROUGH THE PRISM OF STEREOTYPES, PREJUDICE, AND RELIGION: LESSONS FROM NORTH MACEDONIA, BOSNIA AND HERZEGOVINA, AND KOSOVO (Religious dialogue and cooperation, 2024)
Multiple-holistic analysis conducted in the Western Balkans has shown that context(s)in the Western Balkans are overflowed with stereotypes, prejudice, and religious intolerance. Thesethree phenomena were included in extensive multiple-holistic case study by conducting interviewsand open-ended surveys among peace activists, journalists, politicians, as well as members of thecivil society, in the countries of North Macedonia, Bosnia and Hercegovina, and Kosovo. The researchfindings draw a picture of a still deeply prejudiced and divided societies. People categorizeeach other according to their religion and ethnicity. The group they identified themselves with representsthe reference for what is good or bad. Stereotypes and prejudice are deeply rooted in andtransmitted in early childhood experiences, in most cases as a result of family trauma as a consequenceof an earlier conflict. Also, ethnic prejudice are deeply rooted in state systems. Religion inthese contexts plays a crucial but subtle role in designing unstable and divided contexts. It keepsto its own communities and values through exclusion of the others instead of using its power forunifying and tolerance purposes. The presence of deeply rooted stereotypes and prejudice createuncertain societies and uncertainty among people. The conflict contexts in the Western Balkansrequire a serious and sustainable strategy for building relationships among people regardless oftheir ethnicity and religious affiliation in the long term.
Keywords: Western Balkans; stereotypes; prejudice; religion; conflict contexts